E-learning adoption in nursing education: feasibility analysis using the technology acceptance model with a focus on digital and information literacy - Alshammari, Muna; Salifu, Yakubu; Alwadaany, Bader; Ladan, Muhammad Awwal; Abdul, Halima Musa; Alsaber, Ahmad; Abu El-Kass, Sae’d M. (Frontiers in Education, 2025)
IntroductionThis study investigates the factors influencing the adoption and behavioral intention toward eLearning models in nursing education, using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis.MethodsA structured questionnaire was administered to a sample of 65 participants, examining constructs such as Digital Literacy, Information Literacy, Perceived Usefulness, Feasibility of Adopting eLearning, and Performance Expectancy.ResultsReveal that Perceived Usefulness has a significant direct effect on Performance Expectancy (β = 0.384, t = 3.200, p = 0.001) and Feasibility of Adopting eLearning (β = 0.264, t = 2.160, p = 0.031), and indirectly affects Behavioral Intention through Performance Expectancy (β = 0.140, t = 1.967, p = 0.049). Performance Expectancy also significantly influences Behavioral Intention (β = 0.364, t = 2.894, p = 0.004) and Feasibility of Adopting eLearning (β = 0.317, t = 2.479, p = 0.013). However, Information Literacy showed limited influence, with non-significant pathways to both Feasibility (β = 0.161, t = 1.364, p = 0.172) and Performance Expectancy (β = 0.181, t = 1.062, p = 0.288).DiscussionThese findings underscore the importance of perceived usefulness and performance expectations as key predictors of eLearning adoption, with implications for enhancing digital literacy and support frameworks in educational settings.